Relationship between brand equity of sports tourism destination and psychological factors of advertising messages (Case study: Mashhad aquatic Waves Land) - Ali Salehi; Rasool Norouzi Seyed Hossini; Marjan Saffari (Islamic Azad university, Isfahan Branch, 2022)
Objective: Marketing efforts are aimed at influencing consumers ' attitudes. Consumer behavior in sports and events is a process that people choose and use to meet their needs and receive benefits, services, and products associated with sports and sports events. One of the important fields in sport is the emergence of sports tourism as one of the branches of tourism. In the previous studies, it has been shown that attracting tourists without proper marketing and advertising programs is not possible. In other words, advertising is a tool that will be used with the knowledge of tourist areas to tourists and convince them to travel. The aim of this study was to investigate the relationship between the psychological factors of Advertising messages and the brand equity for Aquatic sports tourism destinations. Methodology: The research method was descriptive correlational. The statistical population of this study was all users of the Mashhad Aquatic Waves Land which using the available sampling method according to Morgan table 384 were selected as the statistical sample. To collect the data by using the pleasure and arousal sensations questionnaire used in Mehrabian and Russell (1974) and the brand equity questionnaire used in Aaker (1991) this research was done. Their reliability was calculated by using Cronbach's alpha coefficient for the pleasure of 0.611, arousal of 0.644 brand awareness component was 0.772, brand association component 0.877, brand perceived quality component 0.765, and brand loyalty component 0.820. Data were analyzed by Pearson correlation coefficient and simple and multiple linear regression tests using SPSS-25 software.Results: The results showed that there is a positive and significant relationship between the arousal of advertising, with brand equity components (perceived quality and brand association) in sports tourism destinations and between the arousal of advertising, with brand equity components (brand loyalty and brand awareness) in sports tourism destinations does not have a positive and significant relationship. Also, there is a positive and significant relationship between the pleasures of advertising, with all the components of brand equity (loyalty, perceived quality, brand association, and brand awareness) and sports tourism destinations. Besides, there is a positive significant relationship between perceived pleasure and arousal from advertising messages.Conclusion: As a conclusion selection and manipulation of psychological factors in advertising messages can affect brand equity for aquatic sports tourism destinations.